Pengembangan Instrumen Lembar Kerja Peserta Didik Berbasis Promblem Based Learning Pada Materi Sistem Persamaan Linier Satu Variabel - Neni febriani, Neni Febriani; Sholihah, Fatimasus; Supratman, Moh (Tirai Edukasi : Jurnal Pendidikan, 2024)
This study aims to develop of instrument  Problem Based Learning (PBL)-based Student Worksheet (LKPD) on the topic of Linear Equation in One Variable (SPLSV) for eighth-grade students at SMP IP Darul Hukumaini Jonggat. The research employed Research and Development (R&D) with Borg and Gall’s model, consisting of problem identification, information gathering, product design, expert validation, trials, and revisions. The participants were 7 students from class VIII A (small-scale trial) and 17 students from class VIII B (large-scale trial). Validation by material and media experts showed that the LKPD achieved the "very valid" criteria with an average score of 98.82%. Teachers’ and students’ responses indicated that the product was practical and highly practical in use. Thus, the developed PBL-based LKPD is feasible to be applied as a learning material to improve students’ understanding of SPLSV